2014
DOI: 10.1123/jab.2014-0035
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Single and Double Leg Drop Jumps: Bilateral Deficit, Standardizing Drop Height, and Equalizing Training Load

Abstract: Bilateral deficit is well documented; however, bilateral deficit is not present in all tasks and is more likely in dynamic activities than isometric activities. No definitive mechanism(s) for bilateral deficit is known but an oft cited mechanism is lower activation of fast twitch motor units. The aim of this study was to produce comparable and consistent one and two legged drop jumps to examine bilateral deficit in elite power athletes and elite endurance athletes. Seven power athletes and seven endurance athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…In essence, when left and right limbs were summed and still could not exceed the bilateral score, this demonstrates how challenging unilateral fast stretch-shortening cycle activities are. This is supported by Pain (30) who showed that both endurance and power-based athletes showed a BLF of -3.8 to -13.8% in power during the DJ test. Thus, with a wide variation in BLD scores across tests, it is suggested that this phenomenon is investigated with multiple metrics for each test.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In essence, when left and right limbs were summed and still could not exceed the bilateral score, this demonstrates how challenging unilateral fast stretch-shortening cycle activities are. This is supported by Pain (30) who showed that both endurance and power-based athletes showed a BLF of -3.8 to -13.8% in power during the DJ test. Thus, with a wide variation in BLD scores across tests, it is suggested that this phenomenon is investigated with multiple metrics for each test.…”
Section: Discussionmentioning
confidence: 59%
“…Subjects were also told to maintain full extension throughout the lower-body during the flight phase of the jump. This was to ensure that dropping and jumping procedures were standardized, in line with research conducted by Pain (30). Any deviation from these instructions resulted in a void trial and the trial was retaken Bilateral and Unilateral Standing Broad Jump (SBJ).…”
Section: Bilateral and Unilateral Drop Jump (Dj)mentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral and Unilateral Drop Jumps (DJ). Subjects performed the jumps using a contact mat (Just Jump system, Probotics, Huntsville, Alabama, USA) and started by standing on a box of 30 cm (bilateral) or 15 cm (unilateral) selected as the chosen height to drop from based on previous research (24). With hands fixed on hips throughout the duration of the test, subjects stood on the designated test leg and were instructed to step off the box and land on the contact mat below, with either both legs or one leg depending on the test measure in question.…”
Section: Bilateral and Unilateral Countermovement Jumps (Cmj)mentioning
confidence: 99%
“…Whilst these investigations underline that the magnitude and existence of BLD may be of importance for athletes and practitioners attempting to maximise physical performance, these studies utilised only jumping assessments of BLD. Examination of literature reveals a range of tests used to assess BLD (Škarabot, et al, 2016), with BLD being demonstrated during isometric (Howard & Enoka, 1991;Magnus & Farthing, 2008;Botton, et al, 2013), isokinetic (Brown, Whitehurst, Gilbert, Findley, & Buchalter, 1994;Dickin & Too, 2006), and explosive (Buckthorpe, Pain, & Folland, 2013;Challis, 1998;Pain, 2014) tasks. Furthermore, a large number (e.g.…”
Section: Introductionmentioning
confidence: 99%